Манифестации идентичности в интернете: виртуальные проекции - Зудилина, Надежда Викторовна (НТУ "ХПИ", 2012)
Identity manifestations of a man on the Internet are the virtual identity projections. They consist of virtual "cover "(nickname ,avatar,game character)which can be constructed by choosing its parameters(sex,age,profession and other)and of content which can not be constructed,as it is an identity projection of a man on the Internet.The source of any virtual projections is the identity of a man.Everyone has the onlyidentity .
Keywords: идентичность; актуальность; ситуация; конструирование